2020
DOI: 10.3390/v12010113
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Gamma Modulation of the Local T Cell Response to Alphavirus Encephalomyelitis

Abstract: Infection of mice with Sindbis virus (SINV) provides a model for examining the role of the immune response to alphavirus infection of the central nervous system (CNS). Interferon-gamma (IFN-γ) is an important component of this response, and we show that SINV-infected differentiated neurons respond to IFN-γ in vitro by induction of antiviral genes and suppression of virus replication.To determine the in vivo effects of IFN-γ on SINV clearance and T cell responses, C57BL/6 mice lacking IFN-γ or IFN-γ receptor-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 103 publications
2
16
0
Order By: Relevance
“…Previous studies have also shown that type II and type III IFN responses are critical to the control of acute RNA virus infections in the brain and placenta, respectively [ 23 , 24 , 25 , 26 ]. Recent studies investigating the antiviral response to alphavirus infection of the central nervous system (CNS) have identified IFN-γ and the type II IFN response as being vital for the control of RNA viruses [ 23 , 24 , 25 , 26 , 27 ]. Given that we found differences in type I IFN deficient mice, future studies evaluating the interactions between xrRNA1 mutant ZIKV and type II and III IFN responses will be critical to fully understand the mechanisms of the sfRNA1 function in different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also shown that type II and type III IFN responses are critical to the control of acute RNA virus infections in the brain and placenta, respectively [ 23 , 24 , 25 , 26 ]. Recent studies investigating the antiviral response to alphavirus infection of the central nervous system (CNS) have identified IFN-γ and the type II IFN response as being vital for the control of RNA viruses [ 23 , 24 , 25 , 26 , 27 ]. Given that we found differences in type I IFN deficient mice, future studies evaluating the interactions between xrRNA1 mutant ZIKV and type II and III IFN responses will be critical to fully understand the mechanisms of the sfRNA1 function in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sfRNA1 deficiency does not alter the growth of WNV or DENV in cultured host cells but does result in reduced cytopathic effect and plaque size [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Differential expression of sfRNA isotypes assists in host adaptation for some flaviviruses [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…InterPro sequence analysis [ 26 ] of MGF360-1L revealed that amino acids 99-309 are those that distinguish MGF360-1L as a member of the MGF360 family. Furthermore, MGF360-1L is not detected in the proteome of ASFV viral particles, which would be expected of genes involved in viral DNA replication [ 27 ]. These predicted domains and locations in the genome are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the ZIKV xrRNA1 tertiary structure to construct a mutant with a single nucleotide change that disrupts xrRNA1 structure and eliminates sfRNA1 production without significantly altering the sequence of the ZIKV 3'UTR. We show for the first time that targeted have identified IFN-γ and the type II IFN response as being vital for the control of RNA viruses [20,24]. Given, that we found differences in type 1 IFN deficient mice, future studies evaluating the interactions between xrRNA1 mutant ZIKV and type II and III IFN responses will be critical to fully understand the mechanisms of the sfRNA1 function in different tissues.…”
Section: Discussionmentioning
confidence: 72%